Characterization of hydrothermal aging induced voids in carbon fiber reinforced epoxy resin composites using micro-computed tomography. (December 2022) - Zhuang, Xiangjie; Ma, Junsen; Liu, Fei; Dan, Yi; Huang, Yun; Jiang, Long
Highlights: Micro-computed tomography was performed for voids characterization. Early damage of interface and matrix makes inter-laminar shear strength decrease. Matrix embrittlement by network destruction while chemical structure is unchanged. Abstract: The main aim of this work is the voids characterization of carbon fiber reinforced epoxy resin (CFRP) composites after hydrothermal aging. The composites aged at varying time and temperature were investigated using micro-computed tomography, scanning electron microscope, fourier transform infrared spectroscopy, dynamic mechanical analysis as well as monitoring water uptake and inter-laminar shear strength. It is shown that the porosity increases rapidly in first 45 days while maintains stable in following 105 days. The equilibrium porosity at 35 °C, 55 °C, 75 °C and 95 °C are 0.52%, 0.54%, 0.67% and 0.72% respectively. The strip-like voids and fracture morphology indicate the destruction of interface and resin, but the former is more vulnerable. However, the resin matrix embrittlement is caused by network damage while chemical structure is almost unchanged. As a result, the water diffuses and inter-laminar shear strength deterioration. This study clarifies the influence of voids on structure and properties of CFRP composites and is expected to deepen the understanding of hydrothermal aging mechanism of CFRP composites.